Herbicidal Activity of the Invasive Weed Malachra capitata L.: Growth Stage Dependence, Bioassay-Guided Fractionation, and Physiological Effects on Seed Germination - Pattharin Wichittrakarn; Sirichai Sathuwijarn; Nutcha Manichart; Kaori Yoneyama; Potjana Sikhao; Naphat Somala; Chamroon Laosinwattana (Plants, 2026)
, providing a foundation for further applied research and supporting its valorization for sustainable weed management.
Keywords: Allelopathy and phytotoxic interactions; Weed Control and Herbicide Applications; Chemical synthesis and alkaloids